Pancreatic cancer - Brand, Randall (Henry Stewart Talks, 2011)
General epidemiologic data for pancreatic cancer, Review risk factors for pancreatic cancer, Clinical presentation and diagnostic modalities for pancreatic cancer, Current status for early detection, diagnosis and staging of pancreatic cancer, Treatment of pancreatic cancer
Archived at 2016/09/28